Geo-Congress 2014 Technical Papers 2014
DOI: 10.1061/9780784413272.244
|View full text |Cite
|
Sign up to set email alerts
|

Fiber-Reinforcement Optimization Using a Soil Approach

Abstract: Fiber products can co-exist with natural system and can provide safe, economical, and long-lived composites. Researchers have added polypropylene fiber to soil and determined that it can improve the geotechnical behavior of the soil. However, they followed the same approach currently being used in concrete. In concrete, the amount of fiber added is usually an arbitrarily specified percentage to improve a specific property of the concrete. The percentage usually varies with the intended use of the concrete.Rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Furthermore, the damping ratio decreased with the addition of rubber under low confining pressure (σ c = 50 kPa and 100 kPa) and increased with increase of rubber content under high confining pressure [19]. Moreover, various models and methods related to failure criteria, plastic theory and limit analysis under dynamic loading were developed by many researchers to investigate the dynamic behavior of reinforced soil [3,[20][21][22][23][24][25][26][27][28]. On the other hand, soil reinforcement with different types of fiber plays a significant role in mechanical and thermal properties of soil.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the damping ratio decreased with the addition of rubber under low confining pressure (σ c = 50 kPa and 100 kPa) and increased with increase of rubber content under high confining pressure [19]. Moreover, various models and methods related to failure criteria, plastic theory and limit analysis under dynamic loading were developed by many researchers to investigate the dynamic behavior of reinforced soil [3,[20][21][22][23][24][25][26][27][28]. On the other hand, soil reinforcement with different types of fiber plays a significant role in mechanical and thermal properties of soil.…”
Section: Introductionmentioning
confidence: 99%
“…For a fiber content of 0.2% that exceeds the optimum percentage, the improvement extent became marginal in comparison with the compaction characteristics of pure sand. In fact, Amir-Faryar and Aggour (2014) estimated that extra fibers replace soil particles instead of only filling the voids. Hence, the sand grains cannot be close to each other.…”
Section: Resultsmentioning
confidence: 99%
“…The studies have shown that the improvement extent of fiber-reinforced soils really depends on the adopted fiber content. For instance, the engineering properties of the reinforced mixtures change with various fiber contents ( Amir-Faryar and Aggour, 2012 , 2014 ). Furthermore, the effectiveness of fiber inclusion is considerably dependent on the tested soil ( Patel and Singh, 2017 ).…”
Section: Introductionmentioning
confidence: 99%